Comparative whole-genome analysis reveals artificial selection effects on Ustilago esculenta genome. (19th July 2017) - Ye, Zihong; Pan, Yao; Zhang, Yafen; Cui, Haifeng; Jin, Gulei; McHardy, Alice C; Fan, Longjiang; Yu, Xiaoping
Abstract: Ustilago esculenta, infects Zizania latifolia, and induced host stem swollen to be a popular vegetable called Jiaobai in China. It is the long-standing artificial selection that maximizes the occurrence of favourable Jiaobai, and thus maintaining the plant–fungi interaction and modulating the fungus evolving from plant pathogen to entophyte. In this study, whole genome of U. esculenta was sequenced and transcriptomes of the fungi and its host were analysed. The 20.2 Mb U. esculenta draft genome of 6, 654 predicted genes including mating, primary metabolism, secreted proteins, shared a high similarity to related Smut fungi. But U. esculenta prefers RNA silencing not repeat-induced point in defence and has more introns per gene, indicating relatively slow evolution rate. The fungus also lacks some genes in amino acid biosynthesis pathway which were filled by up-regulated host genes and developed distinct amino acid response mechanism to balance the infection–resistance interaction. Besides, U. esculenta lost some surface sensors, important virulence factors and host range-related effectors to maintain the economic endophytic life. The elucidation of the U. esculenta genomic information as well as expression profiles can not only contribute to more comprehensive insights into the molecular mechanism underlying artificial selection but also into smut fungi–host interactions.